Impact of Beta-Lactam Target Attainment on Resistance Development in Patients with Gram-Negative Infections - Nicole F. Maranchick; Jessica Webber; Mohammad H. Alshaer; Timothy W. Felton; Charles A. Peloquin (MDPI AG, 2023)
Background: The objective was to identify associations between beta-lactam pharmacokinetic/pharmacodynamic (PK/PD) targets and Gram-negative bacteria resistance emergence in patients. Methods: Retrospective data were collected between 2016 to 2019 at the University of Florida Health-Shands Hospital in Gainesville, FL. Adult patients with two Gram-negative isolates receiving cefepime, meropenem, or piperacillin-tazobactam and who had plasma beta-lactam concentrations were included. Beta-lactam exposures and time free drug concentrations that exceeded minimum inhibitory concentrations (ƒT > MIC), four multiples of MIC (ƒT > 4× MIC), and free area under the time concentration curve to MIC (ƒAUC/MIC) were generated. Resistance emergence was defined as any increase in MIC or two-fold increase in MIC. Multiple regression analysis assessed the PK/PD parameter impact on resistance emergence. Results: Two hundred fifty-six patients with 628 isolates were included. The median age was 58 years, and 59% were males. Cefepime was the most common beta-lactam (65%) and Pseudomonas aeruginosa the most common isolate (43%). The mean daily ƒAUC/MIC ≥ 494 was associated with any increase in MIC (p = 0.002) and two-fold increase in MIC (p = 0.004). The daily ƒAUC/MIC ≥ 494 was associated with decreased time on antibiotics (p = 0.008). P. aeruginosa was associated with any increase in MIC (OR: 6.41, 95% CI [3.34-12.28]) or 2× increase in MIC (7.08, 95% CI [3.56-14.07]). Conclusions: ƒAUC/MIC ≥ 494 may be associated with decreased Gram-negative resistance emergence.